How does credit portfolio diversification affect banks’ return and risk? Evidence from Chinese listed commercial banks - Chen, Yibing; Shi, Yong; Wei, Xianhua; Zhang, Lingling (Technological and Economic Development of Economy, 2014)
Does diversification of credit portfolio indeed lead to increased performance and reduced risk of banks as traditional portfolio theory suggests? This paper investigates empirically the effects of diversification on the Chinese banks’ return and risk from the aspect of sector. Panel data on 16 Chinese listed commercial banks during the 2007–2011 period is used for the study. We construct a new diversification measure, taking systematic risk of different sectors into consideration by weighting them with their betas and compare the results with those of more conventional measure HHI. We find that sectorial diversification is associated with reduced return and also decreased risk at the same time, which however, contradicts existing findings in developed countries such as Italy and Germany, and also in emerging economies such as Brazil and Argentina. Our analysis also provides important implication for regulators and policy makers of the banks in emerging markets.